Guidelines on assessing biodiverse foods in dietary intake surveys - Kennedy, G.; Lee, W.T.K.; Termote, Céline; Charrondiere, R.; Yen, J.; Tung, A. (Food and Agriculture Organization of the United Nations, 2017)
FAO produced these guidelines in collaboration with Bioversity International with the aim of facilitating the work of researchers who wish to capture biodiversity aspects (appropriate levels of taxonomic identification of foods) incommonly used dietary surveys, including 24-hour recall, food records, food frequency questionnaires (FFQ) and dietary diversity surveys. For the sake of simplicity, these guidelines focus on plant foods, which is where the expertise of Bioversity International lies, but similar principles could be applied to animal foods, insects, fish and other aquatic species, with the support of appropriate experts. The guidelines are intended as a practical tool, and describe the preparatory steps involved in assessing and documenting local foods, with appropriate levels of detail in taxonomic identification.This is followed by suggestions on how to adapt dietary assessment instruments to collect information on biodiverse foods.